2015
DOI: 10.1038/srep14517
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacogenetics of Complement Factor H Y402H Polymorphism and Treatment of Neovascular AMD with Anti-VEGF Agents: A Meta-Analysis

Abstract: The purpose of this study is to investigate whether the Y402H polymorphism (rs1061170, a T-to-C transition at amino acid position 402) in the complement factor H (CFH) gene have a pharmacogenetics effect on the anti-vascular endothelial growth factor (VEGF) treatment for neovascular age-related macular degeneration (AMD). We performed a meta-analysis using databases including PubMed and EMBASE to find relevant studies. 13 published association studies were selected for this meta-analysis, including 2704 patien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
18
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(21 citation statements)
references
References 45 publications
2
18
1
Order By: Relevance
“…Pooled analysis indicated that CFH risk genotypes were weakly but significantly associated with less effective response to any form of treatment, including anti-VEGF agents, photodynamic therapy, and antioxidants/zinc supplementation [ 32 ]. This finding was further confirmed by more specific meta-analyses of studies, investigating the relationship between CFH rs1061170 polymorphism and response to anti-VEGF treatment [ 97 , 173 ].…”
Section: Interaction Of Genetic Variants With Amd Treatmentsmentioning
confidence: 63%
“…Pooled analysis indicated that CFH risk genotypes were weakly but significantly associated with less effective response to any form of treatment, including anti-VEGF agents, photodynamic therapy, and antioxidants/zinc supplementation [ 32 ]. This finding was further confirmed by more specific meta-analyses of studies, investigating the relationship between CFH rs1061170 polymorphism and response to anti-VEGF treatment [ 97 , 173 ].…”
Section: Interaction Of Genetic Variants With Amd Treatmentsmentioning
confidence: 63%
“…These effects were more pronounced in cells expressing CFH 402H, possibly because they already have reduced complement regulatory capacity and anti-VEGF treatment could decrease this further. This could explain why the CFH 402H polymorphism has been reported to correlate with a reduced response to anti-VEGF therapy (19, 45, 46), although in this complex disease, it is likely that several other factors also contribute to the variable response to anti-VEGF therapy (47). Furthermore, while controversial, there are patient studies suggesting that VEGF antagonists may enhance progression of GA (8, 9, 48, 49), which could be related to direct complement-mediated damage of the RPE cells.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, complete VEGF inhibition may be detrimental, but given the variability in reported effects, modifying factors could influence patient response and risk of developing side effects. A recent meta-analysis combining 13 studies reported reduced response to anti-VEGF therapy in patients homozygous for the complement factor H (CFH) polymorphism Y402H (19). The reason why these patients respond less well is unclear, but could suggest a relationship between VEGF and complement.…”
Section: Introductionmentioning
confidence: 99%
“…With the increasing use of anti-VEGF agents in treating nAMD, a growing number of studies has been investigating the association between the patient response to treatment and specific gene variants [22,23]. Among the genes linked to the development of nAMD, CFH Y402H polymorphism has been studied most extensively, although with contradictory findings in different populations [24].…”
Section: Discussionmentioning
confidence: 99%